2023
DOI: 10.1039/d3fo02580b
|View full text |Cite
|
Sign up to set email alerts
|

The anti-aging mechanism of ginsenosides with medicine and food homology

Tiantian Tian,
Chung-Nga Ko,
Wenya Luo
et al.

Abstract: With the acceleration of global aging and the rise in living standard, the achieving of healthy aging is becoming an imperative issue globally. Ginseng, a medicinal plant that has a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 136 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…22 The primary pharmacologically active compounds extracted from ginseng have diverse bioactive functions encompassing anti-carcinogenic, anti-aging, anti-inflammatory and antioxidant properties. 23–26 Among these compounds, Ginsenoside-Rb2 (Rb2), the most abundant saponin identified in ginseng, has shown potential anti-osteoporosis effects according to a previous study. It has been reported that Rb2 inhibited osteoporosis induced by a ketogenic diet in mice.…”
Section: Introductionmentioning
confidence: 99%
“…22 The primary pharmacologically active compounds extracted from ginseng have diverse bioactive functions encompassing anti-carcinogenic, anti-aging, anti-inflammatory and antioxidant properties. 23–26 Among these compounds, Ginsenoside-Rb2 (Rb2), the most abundant saponin identified in ginseng, has shown potential anti-osteoporosis effects according to a previous study. It has been reported that Rb2 inhibited osteoporosis induced by a ketogenic diet in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is mainly characterized by a progressive dysfunction of metabolism and various physiological roles. PDS and PTS are important antiaging drugs that could promote the metabolism and proliferation of stem cells, protect the skin, brain, heart, and nerves, enhance mitochondrial function and telomerase activity, and maintain the intestinal flora [ 46 ]. Xu et al reported that Rb1 and Rg1 reduced ROS production, increased CAT activity, elevated the mtDNA content and ATP level, and attenuated the MMP depolarization of primary mouse astrocytes injury induced by oxygen-glucose deprivation/reoxygenation (OGD/R).…”
Section: Pharmacological Effects and Mechanisms Of Pds And Ptsmentioning
confidence: 99%
“…TA-65, a compound containing cycloastragenol isolated from A. membranaceus roots, has been shown to increase telomerase activity in embryonic fibroblasts, inhibit DNA damage, and enhance immune function [ 22 , 23 ]. Ginseng is a valuable traditional Chinese medicine that contains ginsenosides, which are among the most important active ingredients for its anti-aging function [ 24 ].…”
Section: Introductionmentioning
confidence: 99%